2021
DOI: 10.1111/os.12953
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of Early Ambulation in Elderly Patients Undergoing Lumbar Decompression and Fusion Surgery: A Prospective Cohort Study

Abstract: Objective: To evaluate the effects of early ambulation on elderly patients' postoperative physical functional outcomes, complications, 90-day readmission rate, and the length of postoperative hospital stay.Methods: This is a prospective cohort study conducted between June 2019 and December 2019. The study enrolled 86 elderly patients (39 males) with newly diagnosed lumbar degenerative disease undergoing single-segment decompression and fusion surgerywere enrolled. Of all 86 patients, 39 voluntarily joined the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…4 Similarly, Hueng et al demonstrated that elderly patients who ambulated within 4 hours after lumbar decompression and fusion had lower rates of postoperative ileus and urinary retention compared with those who were able to ambulate between 4 and 24 hours. 5 Adogwa et al described lower incidence of pneumonia and overall postoperative complications among elderly ASD patients who ambulated early on during their postoperative course. 8 Several studies have expanded upon the effect of postoperative mobility by examining patient-reported outcomes and quality of life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Similarly, Hueng et al demonstrated that elderly patients who ambulated within 4 hours after lumbar decompression and fusion had lower rates of postoperative ileus and urinary retention compared with those who were able to ambulate between 4 and 24 hours. 5 Adogwa et al described lower incidence of pneumonia and overall postoperative complications among elderly ASD patients who ambulated early on during their postoperative course. 8 Several studies have expanded upon the effect of postoperative mobility by examining patient-reported outcomes and quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated the effect of ambulation in the first week after spine surgery on long-term patient disability, physical function, and postoperative complications; however, the relationship between inpatient physical activity after ASD surgery and postoperative complications in elderly patients has not been fully explored. [3][4][5][6][7][8][9][10][11][12][13][14] The ability of the elderly patient to independently walk as early as possible following ASD surgery may decrease the perioperative complication rate. The present study examines the correlation in clinical outcomes of elderly patients with their ability to ambulate.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional fasting for 8 h before surgery and eating for 1 day after surgery may lead to insulin resistance and metabolic stress, and metabolic stress may also increase the incidence of postoperative complications [22,23]. In ERAS concept, early ambulation is an important item, which can reduce the incidence of deep vein thrombosis, promote exhaust, shorten the LHS, and reduce the mortality [24,25]. Shortening fasting and early postoperative feeding can improve the metabolic status of patients, enhance resistance, and help patients recover their appetite and shorten the LHS [26].…”
Section: Discussionmentioning
confidence: 99%
“…The outcome variable (continuous variable) was obtained following the previously published guidelines and studies ( 1 , 4 , 5 , 15 , 16 ). In addition, the time to first ambulation was measured as follows: a registration form for the time to first mobilization was distributed upon admission to the hospital and the patient would walk for at least 15 min after getting out of bed for the first time ( 3 , 17 ).…”
Section: Methodsmentioning
confidence: 99%
“…However, there is no standard definition of the time to first ambulation. Previous studies reported that the time to early ambulation may range from 4 h after surgery to 6 h post operation ( 2 – 4 ). Although these studies pointed out the the time horizon to early ambulation, they did not define occurrence of mobilization events ( 1 , 4 , 5 ).…”
Section: Introductionmentioning
confidence: 99%